Antiarrhythmic effects of vernakalant in human-induced pluripotent stem cell-derived cardiomyocytes from a patient with short QT syndrome type 1 - Xu, Qiang; Huang, Xuemei; Meng, Zenghui; Li, Yingrui; Zhong, Rujia; Li, Xin; Cyganek, Lukas; El-Battrawy, Ibrahim; Akın, Ibrahim; Zhou, Xiao-Bo; Lan, Huan (Journal of cardiovascular development and disease, 2022)
(1) Background: Short QT syndrome (SQTS) may result in sudden cardiac death. So far, no drugs, except quinidine, have been demonstrated to be effective in some patients with SQTS type 1 (SQTS1). This study was designed to examine the potential effectiveness of vernakalant for treating SQTS1 patients, using human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) from a patient with SQTS1. (2) Methods: Patch clamp and calcium imaging techniques were used to examine the drug effects. (3) Results: Vernakalant prolonged the action potential duration (APD) in hiPSC-CMs from a SQTS1-patient (SQTS1-hiPSC-CMs). In spontaneously beating SQTS1-hiPSC-CMs, vernakalant reduced the arrhythmia-like events induced by carbachol plus epinephrine. Vernakalant failed to suppress the hERG channel currents but reduced the outward small-conductance calcium-activated potassium channel current. In addition, it enhanced Na/Ca exchanger currents and late sodium currents, in agreement with its APD-prolonging effect. (4) Conclusions: The results demonstrated that vernakalant can prolong APD and reduce arrhythmia-like events in SQTS1-hiPSC-CMs and may be a candidate drug for treating arrhythmias in SQTS1-patients.